Роль восприятия технологического прогресса в развитии общества на примере Китая - Кулик, Ю. В. (БНТУ, 2025)
Research dedicated to the issue of the perception of technologies impact on the science and technology development of the society. On the statistic data of China is demonstrated the correlation between society’s attitude towards technologies and benefits of their implantation.